Aortic Clamping Time Is Associated With Postoperative Thrombocytopenia Following Elective Open Abdominal Aortic Surgery - Victor Bilman; Jonathan Alk; Moshe Halak; Chen Speter; Ophira Salomon; Daniel Silverberg (International Journal of Vascular Medicine)
Conclusion: Postoperative thrombocytopenia is common following an elective abdominal aortic surgery, but it was demonstrated that it typically resolves on its own by POD 5 without significant clinical consequences. The study identified the patient age, and aortic clamping time as independent risk factors for the development of thrombocytopenia. However, further research involving larger cohorts is needed to confirm these findings and better understand the underlying mechanisms and potential implications.